Analisis Perkembangan Manajemen Zakat untuk Pemberdayaan Masyarakat di Indonesia - Munif Solikhan (JURNAL ILMIAH SYI'AR, 2020)
This study aims to analyze the management of zakat for community empowerment in Indonesia, the potential of zakat currently in Indonesia is quite large, reaching hundreds of trillions of rupiah. However, the impact of zakat funds has not been felt optimally by the wider community. Actually, historically, zakat management has existed since Islam entered this country, continued into the colonial era, the era of independence during the new order and then continued in the reformation period. Management of zakat runs quite massive when the government issued Law No. 38 of 1999 concerning zakat management. Amil Zakat Institutions began to appear and compete to issue programs to help find solutions to community problems. In this paper the management of zakat is divided into two namely consumptive zakat and productive zakat. Both of these zakat have the same purpose which is to empower the community. In the consumptive zakat, zakat funds are used to help people who are direct, temporary and urgent, such as living, education, health and other assistance. Whereas in productive zakat, zakat funds are distributed by empowering the community in a sustainable manner, such as providing capital, providing training, and buying production equipment and several other programs. Even though it is felt that the management of zakat is not optimal at the moment, it has helped a little problems in the community.